Pengaruh Minat, Motivasi, Penghargaan Finansial, dan Pengetahuan tentang Pajak Terhadap Pilihan Berkarir di Bidang Perpajakan (Studi pada Mahasiswa Akuntansi yang Mengikuti Program Relawan Pajak): (Studi pada Mahasiswa Akuntansi yang Mengikuti Program Relawan Pajak) - Ritayanti, Ni Made; Riesty Masdiantini, Putu (Universitas Pendidikan Ganesha, 2022)
Abstract This research aims to determine the effect of interest, motivation, financial rewards, and knowledge about taxes on career choices in taxation. This type of research is research using a quantitative approach. This research data collection method uses a questionnaire, literature study, and documentation. Sources of data used are primary data and secondary data. Primary data was obtained from the results of the questionnaire data processing, while secondary data were obtained from data on the number of tax volunteers at the Regional Office of DJP Bali and various supporting literature. The sample of this research was 97 respondents who were selected based on the purposive sampling technique. The results of this research indicate that interest, motivation, and knowledge about taxes had a positive and significant effect on career choices in the field of taxation. Meanwhile, financial rewards do not have effect on career choices in the field of taxation. This means that financial rewards are not the main reason for S1 accounting students who attend the tax volunteer program to choose a career in taxation. Keywords : career, taxation, tax volunteer